International Labour Law Reports - Weiss, Dimitri (Relations Industrielles / Industrial Relations, 1979)
This article reviews the book, "International Labour Law Reports," by Zvi H. Bar-Niv, Benjamin Aaron, Thilo Ramm, Fokle Schmidt, Jean Maurice Verdier, Kenneth William Wedderburn, Peter Elman, Alphen ann den Rijn, Sijthoff & Noordhoff, Edited.